CLINICO-MICROBIOLOGICAL PROFILE OF COMMUNITY ACQUIRED PNEUMONIA IN A TERTIARY CARE HOSPITAL - MANTHALE2Dr. BOMA GIRIRAJ1*, Dr. DEEPAK (Journal of Biomedical and Pharmaceutical Research, 2017)
Community Acquired Pneumonia (CAP) is a frequently encountered lower respiratory tract parenchymal lung infection which continues to be a major health problem leading to significant morbidity and mortality worldwide. Etiology of CAP is generally bacterial but the microbial pattern varies geographically. Some of the studies conducted in India have reported Streptococcus pneumoniae as the most common causative agent and others have reported Pseudomonas aeruginosa as the common pathogen. The choice of empirical therapy for CAP has become complicated by the rapid development of drug resistance to commonly used drugs. The resistant strains of bacteria can quickly multiply and spread within the community. This was a retrospective study conducted in a tertiary care hospital in South India from May 2011 to April 2013. The cases were recorded from the Microbiology laboratory. A total of 136 cases were included for analysis. Maximum case was in males and in age group of 51-60 years. Most common symptoms/signs were Cough, Fever, Crepitations and Bronchial breath sound. Most common organism isolated was Streptococcus pneumoniae followed by Pseudomonas aeruginosa and Klebsiella pneumoniae. The overall microbial diagnosis of CAP was confirmed in 33.8% . Choosing the proper antibiotics as initial empiric therapy & later streamlining as per the culture sensitivity pattern is critical in outcome of CAP. Important considerations include penetration into respiratory secretions, spectrum of activity and antimicrobial resistance. Gram negative bacilli as a group are more common than S. pneumoniae. P. aeruginosa is the most common organism among the Gram negative bacilli. Microbiological profile of CAP varies geographically. There is a need to conduct regular prevalence and antibiogram studies to develop empirical guidelines for treatment of CAP in that particular region. Key words: Community acquired pneumonia, Streptococcus pneumoniae, Sputum culture, Microbiological profile